The effect of tibia perforation on the strength of humerus in juvenile rats with streptozotocin-induced diabetes - A.V. Torba (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2022)
Background. The purpose of the research is to investigate the dynamic changes of humerus strength in juvenile streptozotocin-induced diabetic rats after surgical perforation of the tibia. Materials and methods. Diabetes (35 animals with body weight of 135-150 g at the age of 3 months) was induced by a single intraperitoneal injection of streptozotocin in dosage of 55 mg per kg of body weight. Surgical perforation of the tibia was modeled as 2 mm through opening in the proximal metadiaphysis (35 animals). Another group comprised 35 animals with both perforation and diabetes. 35 intact animals comprised the control group. Strength testing was performed by means of three-point bending loading technique at a loading speed of 10 μm per minute. Strength features were calculated from resulting displacement curves. Results. Surgical perforation of the tibia results in decrease of strength of the humerus; manifestations peak was observed on the 30th day after intervention. By the 30th day elasticity modulus, ultimate strength, and fracture energy were lower than those of the controls by 10.83 %, 13.47 %, and 13.60 % (hereinafter, all the given numerical differences are statistically significant, p≤0.05). In streptozotocin-induced diabetes humerus strength features depend on duration of the experiment. By the 90th day ultimate strength, elasticity modulus, and fracture energy were lower than those of the controls by 11.97 %, 4.53 %, and 10.59 %. Fracture of the tibia in streptozotocin-induced diabetes leads to aggravation of strength disorders beginning from the 7th day of observation. By the 90th day elasticity modulus, ultimate strength, and fracture energy decreased by 10.74 %, 9.08 %, and 8.22 % respectively (in comparison with non-diabetic animals with fracture of the tibia). Conclusions. Surgical perforation of the tibia in streptozotocin-induced diabetic juvenile rats leads to aggravation of humerus strength disorders from the 7th day after intervention.